1998
DOI: 10.1006/viro.1998.9397
|View full text |Cite
|
Sign up to set email alerts
|

Marker Rescue of the Host Range Restriction Defects of Modified Vaccinia Virus Ankara

Abstract: The severely attenuated and host range (HR) restricted modified vaccinia virus Ankara (MVA) was derived by >500 passages in chick embryo fibroblasts, during which multiple deletions and mutations occurred. To determine the basis of the HR defect, we prepared cosmids from the parental vaccinia virus Ankara genome and transfected them into nonpermissive monkey BS-C-1 cells that had been infected with MVA. Recombinant viruses that formed macroscopic plaques were detected after transfections with DNA segments that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 40 publications
3
79
0
Order By: Relevance
“…The block in replication occurs at a late step in virus assembly (6,13) and is caused by multiple gene defects (16). Because of its extreme attenuation, no adverse effects were reported even when high doses of MVA were given to immune-deficient non-human primates (17).…”
mentioning
confidence: 99%
“…The block in replication occurs at a late step in virus assembly (6,13) and is caused by multiple gene defects (16). Because of its extreme attenuation, no adverse effects were reported even when high doses of MVA were given to immune-deficient non-human primates (17).…”
mentioning
confidence: 99%
“…In consequence, MVA shows a characteristic growth deficiency phenotype upon in vitro infection with unimpaired viral protein synthesis in all human cells being tested. 41,[43][44][45] Moreover, the in vivo inoculation of MVA goes along with a strong stimulation of innate host responses resulting in the synthesis of type I interferons, CC chemokines, and in the attraction of host leukocytes to the site of injection. 46,47 Since other studied VACV strains seem not to have similar immunostimulatory capacities this feature is unique to MVA and might contribute to the potency of MVA based vaccines.…”
Section: The Different Generations Of Vaccinesmentioning
confidence: 99%
“…The suspension was then centrifuged (454). Although poxviruses possess well-organized replication machinery that allow them to infect a wide spectrum of eukaryotic hosts in vitro, some poxviruses are host restricted (173,174,192,215,286,288,421,670,763). In these restrictive cells, poxviruses efficiently enter target cells, but fail to complete their replicative life cycle.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…In a subsequent publication, Johnston et. al identified a role for the serine-threonine kinase, PAK-1, in myxoma virus replication, and suggested that the permissiveness of target cells to infection resides in their ability to activate this kinase (314 Although VACV infects a variety of cells, some poxviruses fail to grow in certain host cells in vitro, a phenomenon known as host restriction (173,174,192,215,286,288,421,670,763). In these restrictive cells, poxviruses enter the cell efficiently but fail to replicate.…”
Section: In Vitro Vacv Infectionmentioning
confidence: 99%